Assessing the Accuracy of Global Canopy Height Models: A Comprehensive Review - Lencinas, José Daniel (Bosque (Valdivia), 2025)
Accurate measurements of canopy heights play a pivotal role in estimating vegetation biomass. The Advanced Topographic Laser Altimeter System (ATLAS), and the Global Ecosystem Dynamics Investigation (GEDI) have significantly improved LiDAR capability for three-dimensional mapping. Global canopy height maps were released at medium to very high spatial resolutions: Land and Vegetation Height (ATLAS-ATL08 product), Global Forest Canopy Height Map (GFCH), the High-Resolution Canopy Height Model of the Earth (HRCH), and Global Map of Tree Canopy Height (GMTCH). This study aimed to provide a review of the accuracy assessment results of the recent global canopy height maps, by comparing them with independent airborne laser scanning (ALS) data. According to the findings, global canopy height models were mainly validated in boreal and temperate forests, primarily in North America, Europe, and Oceania. ATL08 canopy heights underestimated canopy heights in most cases, reporting mean errors (MEs) less than -2.3 m, and root mean square errors (RMSEs) ranging from 2.9 m to 7 m. GFCH showed larger negative vertical offsets with MEs ranging from -3.8 m to -14 m (RMSEs 9 m - 18 m). On the other hand, HRCH tended to overestimate (MEs 1,7 m - 6.0 m, RMSEs 8 m - 11 m) most forested areas. GMTCH consistently underestimated the height of all canopies with MEs ranging from -7 m to -12 m (RMSEs 10 m - 17 m). Recommendations are provided to enhance the global availability of independent ALS data, and potential application for the maps are recognized.